Siccia imana, a new species from Rwanda (Lepidoptera: Erebidae: Arctiinae) - Volynkin, Anton V. (Zootaxa, 2019)
The genus Siccia Walker, 1854 is a member of the subtribe Cisthenina Bendib & Minet of the tribe Lithosiini Billberg (family Erebidae Leach, subfamily Arctiinae Leach) being widely distributed in the Afrotropics. Members of the genus are small or medium-sized moths with similar external appearance (whitish or grey wing coloration with blackish pattern consisting of spots and transverse lines). The check-list of the genus was provided by Kühne (2007), two additional species were described by Ivinskis & Saldaitis (2008). Currently the genus includes 20 valid species with very different male and female genitalia structures, and the generic and subgeneric structure of this group needs revision (Volynkin & László, in prep.).